Current trends of genetics in apical periodontitis research - Erika Calvano Küchler; Jardel Francisco Mazzi-Chaves; Leonardo Santos Antunes; Christian Kirschneck; Flares Baratto-Filho; Manoel Damião Sousa-Neto (Sociedade Brasileira de Pesquisa Odontológica, 2018)
Abstract: Genetics is an emerging topic in endodontic research focusing on the host response regarding the pathogenesis of apical periodontitis (AP). A number of genetic epidemiological studies carried out by many investigators worldwide have shown evidence of an association between certain candidate genes and AP. Some studies have been conducted on knockout mice with a deficiency in certain proteins, leading to more or less severe AP, and thus suggesting a pivotal role of these genes in AP pathogenesis. Other research has evaluated the association between genetic polymorphisms in humans with different AP aspects; these studies pointed out that genetic polymorphisms in some candidate genes are involved in inter-individual variations in their response to AP. Therefore, the objective of this report was to provide an updated overview of the genes involved in AP pathogenesis, with a focus on the most relevant candidate genes.